Persepsi Konsumen terhadap Beras Organik Mentik Susu - Ida Ayu Made, Dwi Susanti (UNIVERSITAS LANCANG KUNING, 2023)
Mentik Susu organic rice is a type of organic rice cultivated by Balinese people, especially in Sidan Village, Gianyar Regency which is marketed through Sidan BUMDES. This study aims to determine the level of consumer satisfaction of Mentik Susu organic rice on the 4P and to determine aspect the relationship between consumer characteristics and the level of consumer satisfaction of Mentik Susu organic rice food products and. This type of research is qualitative and quantitative. The research instrument used was interviews and questionnaires. The data analysis technique uses descriptive data with 4 aspects namely: product, price, place, promotion. The results showed that there was no significant relationship between customer characteristics (age, education, gender and income) with the level of satisfaction with Mentik Susu food products and Mentik Susu rice consumers felt very satisfied (SP) with a percentage of 84.41% of the product, price , place and promotion applied to Mentik Susu food products.